The New .Africa Top Level Domain: An African Initiative in Ensuring Africa’s Rightful Place on the Global Network - Hurter, Eddie; Pistorious, Tana (Potchefstroom Electronic Law Journal, 2017)
The new gTLD programme of the Internet Corporation for Assigned Names and Numbers (ICANN) is the single most important development since the privatisation of the DNS in 1998. The management of the Domain Name System (DNS) has developed from a modest undertaking to its current explosive expansion through the new gTLD programme. Africa has boldly entered the arena through the delegation of the .Africa gTLD. This new development heralds an innovative era in the management of the DNS, especially for Africa. The dotAfrica gTLD launch strategy offers several advantages to African governments and traders alike. One of the innovative features of the management of dotAfrica is the fact that a broader set of rights including commercial, cultural, linguistic, religious and personal rights will be protected. Furthermore, African trade mark proprietors and other rights holders are protected, initially at least, by various innovative rights-protection mechanisms. This development is important for African governments and it should form an integral part of right holders’ intellectual property management strategy.